Physical Activity, Nutritional Status, Basal Metabolic Rate, and Total Energy Expenditure of Indonesia Migrant Workers during Covid-19 Pandemic - I Putu Agus Dharma Hita; B. M. Wara Kushartanti; Fitri Agung Nanda (Universitas Pendidikan Indonesia, 2020)
Physical activity, nutritional status, and total energy expenditure are important components of a human. The purpose of this study was to find out the depiction of physical activity, nutritional status, basal metabolic rate, and total energy expenditure of Indonesia migrant workers during Covid-19 pandemic. The study was a survey study with a descriptive design. The samples were 86 Indonesia migrant workers. The instrument used was the 24 hour recall physical activity sheet for 14 days. The result of the study showed that: 88% of male samples and 95% of female samples gained physical activity level score in low category. The PAL score of the male samples was 1.56, while the PAL score of female samples was 1.52. Related to body mass index, 51% of Indonesia migrant workers were in the normal category; 27% were in the overweight category; 17% were in the Obese I Category, and 5% were in the Obese II category. 22 Indonesia migrant workers in overweight category had low physical activity category, 15 persons in Obesity I category had low physical activity category, and 4 persons in Obese II category. The average of the BMR of the samples during the quarantine, due to Covid-19 pandemic, was 1669 kkal/day for male and 1335 kkal/day for female. The average of total energy expenditure of the samples during Covid-19 quarantine was 2595 kkal/day for male and 2031 kkal/day for female. The physical activity level was low, the nutrition status was normal, total energy expenditure was low, the BMR of the sample was dominated by age factor, sex, and weight of the sample. The result of the study was expected to be a reference of regional and other quarantine systems to improve the immunity system during the 14 days of quarantine.